INTRAOCULAR PRESSURE MEASUREMENT: GOLDMANN APPLANATION TONOMETER VS NON CONTACT AIRPUFF TONOMETER - Shah, Masood Alam; Saleem, Khalid Bin; Mehmood, Talat (Journal of Ayub Medical College Abbottabad, 2012)
Background: An accurate assessment of Intraocular pressure (IOP) is vital in establishing diagnosis of Glaucoma and decision making regarding various treatment modalities available. The purpose of this study is to compare Goldmann Applanation Tonometer (GAT) with Air puff tonometer. Methods: Cross-sectional comparative study conducted. 73 eyes from 73 patients were included in this study and intraocular pressure (IOP) was measured by GAT and PT100 at Sheikh Khalifa Bin Zayed Hospital, Muzaffarabad, Benazir Shaheed Teaching Hospital, Abbottabad. Results: Mean age of the patients was 53.17±13.80 years. Mean IOP measurements showed significant differences in measurements performed by the two tonometers (p<0.05). Correlation revealed significant relation between PT100 and GAT (Pearson’s correlation 0.715, p<0.01). Conclusions: Compared to non-contact air-puff tonometer, the Goldmann applanation tonometer is a reliable and consistent technique for measurement of intraocular pressure. Keywords: Glaucoma, Intraocular pressure, Goldmann applanation tonometry, Non-contact air puff tonometer